A handover algorithm in the converged networks of CMMB and TD-MBMS. (1st January 2014) - Liao, Jifeng; Yang, Xiaodong
With the development of information technology, the video services have become one of the most prevalent services in the era. Meanwhile, mobile TV technology has gradually become much more mature in China. In this paper, we first introduce the network architecture of time division-multimedia broadcast multicast service (TD-MBMS) and China Mobile Multimedia Broadcasting (CMMB). Then, we make a comparison of these two standards. As a solution, we propose architecture of converged networks based on these two standards and present a handover algorithm based on the converged network architecture proposed. At the end of this paper, we utilise OPNET for the simulation in order to illustrate the performance of the proposed handover algorithm.